Expression and Characterization of the Novel Gene fr47 during Freezing in the Wood Frog, Rana sylvatica - Katrina J. Sullivan; Kyle K. Biggar; Kenneth B. Storey (Biochemistry Research International)
The wood frog, Rana sylvatica, has numerous adaptations that allow it to survive freezing of up to 65% of its total body water during the winter. Such adaptations have been found to include the expression of novel freeze responsive genes that are thought to be important for adaptation and survival. In this study, the tissue-specific stress responsive expression of one novel gene, fr47, was assessed in seven wood frog tissues. In response to freezing, the transcript expression of fr47 increased significantly in six tissues: heart, lung, liver, skeletal muscle, kidney, and testes. The expression of fr47 was also strongly upregulated by component stresses of freezing, namely, anoxia and dehydration. A dynamic change in fr47 expression was also observed during tadpole development, with expression low in embryonic stages (Gosner stages 14–20), increasing through intermediate (stages 26–43) and transformation phases (stages 44-45). These results indicated that fr47 potentially has a role to play in development and metamorphosis, in addition to freeze, anoxia, and dehydration tolerance. De novo analysis of FR47 protein structure revealed a likelihood of membrane associated function and possible GRB2 association. It is hypothesized that this interaction may influence inositol 1,4,5-trisphosphate production, known to increase during wood frog freezing.